NPS PERFORMANCE AND SOCIAL SECURITY SUSTAINABILITY (International Journal of Food and Nutritional Sciences, 2022)
This research paper is an attempt to analyze the performance of National Pension S based on the number of subscribers, total contribution, and Asset Under Management (AUM) by contributing sectors. The examination of performance is for the period of five years based on data released by PFRDA for the years 2017 to 2022. Percentage, Ranking, and year-on-year comparison methods are used for analysis. The result suggests that Central (CG) and State (ST) Governments are prominent contributors but their subscriber rate is declining, Unorganised sector has shown steepen decline in the number of subscribers, NPS Swavalamban has negative performance during the study period. The Corporate sector has performed exceptionally for the parameters to examine. The overall declining trend in pension products shows lost ground in reality to attract subscribers, and contributors, however, the AUM has surpassed $95 billion.